The Use of Modeling Strategy in Improving Students’ Descriptive Texts Comprehension - Evi Suzanna Evi Suzanna; Nuzulul Isna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The aim of this research is to examine how well the modeling method improves EFL students' understanding of descriptive texts. A total of fifty-nine seventh-grade students from SMPN 2 Susoh were split into experimental and control groups for this quasi-experimental study. Traditional training was given to the control group, whereas the experimental group was taught a modeling method that included four stages: text modeling, deconstruction, co-construction, and self-construction. SPSS version 26, which featured independent samples t-tests, normality, homogeneity, and descriptive statistics, was utilized to assess the data. The experimental group improved by an average of 40.62 points on the post-test, whereas the control group improved by 39.71 points, according to the results. Statistical significance was achieved by the change (p =.042). As a result, the modeling technique has a somewhat positive effect on students' comprehension and composition of descriptive texts. These findings imply that the modeling strategy provides a methodical and successful teaching approach for junior high school English instruction, especially in the setting of EFL.